Seroprevalence of Avian Infl uenza (subtype H9) in ducks at AI risk areas of Nepal - Pradhan, N.R.; Singh, S.; Acharya, M.P. (Nepalese Veterinary Journal, 2018)
A study was conducted in duck population of Nepal from August-2013 to March-2014 as to find out the seroprevalence of Low pathogenic Avian Influenza (LPAI) subtype H9. Altogether 300 blood samples were taken from avian influenza risk areas of Nepal by using purposive sampling method and were analyzed in virology laboratory, Animal Health Research Division, NARC, Khumaltar. The serum samples were processed for Haemagglutination Inhibition (HI). Of the 300 serum samples, 16 samples showed HI positive (at>3rd well) at two-fold dilution revealing revealing 5% Seroprevalence of LPAI H9 and overall average antibody titre 6.27. The seroprevalences of six districts were found to be Chitwan (10%), Sunsari (6%), Kathmandu (2%), Banke (8%), Bhaktapur (2%) and Jhapa (4%) with their mean antibody titres in log form were found to be 6.8, 6.3, 5, 6, 6 and 6.5 respectively. These samples when categorised into three divisions of influenza risk areas viz. Buffer zone, Border market area and Outbreak area, the seroprevalence were found to be 8%, 6% and 2% and their mean antibody titre in log2 form were found to be 6.6, 6.3 and 5.5 respectively. The statistical analyses revealed that there is significant difference (P<0.05) in age wise prevalence on group above 6 months and below 6 months. However, no significant difference (p>0.05) occurred in prevalence by district, sex and influenza risk area.